Fully inkjet-printed biosensors fabricated with a highly stable ink based on carbon nanotubes and enzyme-functionalized nanoparticles - Mass, M. (2021)
Enzyme inks can be inkjet printed to fabricate enzymatic biosensors. However, inks containing enzymes present a low shelf life because enzymes in suspension rapidly lose their catalytic activity. Other major problems of printing these inks are the non-specific adsorption of enzymes onto the chamber walls and stability loss during printing as a result of thermal and/or mechanical stress. It is well known that the catalytic activity can be preserved for significantly longer periods of time and to harsher operational conditions when enzymes are immobilized onto adequate surfaces. Therefore, in this work, horseradish peroxidase was covalently immobilized onto silica nanoparticles. Then, the nanoparticles were mixed into an aqueous ink containing single walled carbon nanotubes. Electrodes printed with this specially formulated ink were characterized, and enzyme electrodes were printed. To test the performance of the enzyme electrodes, a complete amperometric hydrogen peroxide biosensor was fabricated by inkjet printing. The electrochemical response of the printed electrodes was evaluated by cyclic voltammetry in solutions containing redox species, such as hexacyanoferrate (III/II) ions or hydroquinone. The response of the enzyme electrodes was studied for the amperometric determination of hydrogen peroxide. Three months after the ink preparation, the printed enzyme electrodes were found to still exhibit similar sensitivity, demonstrating that catalytic activity is preserved in the proposed ink. Thus, enzyme electrodes can be successfully printed employing highly stable formulation using nanoparticles as carriers.